Effect of cigarette smoking on sleep quality of non-obese male medical students of south Punjab - Bukhari, Syed Mohsin Raza; Mehdi, Ali; Mehdi, Hassan; Nasir, Ghulam Mujtaba; Abbas, Esha; Safdar, Sania; Ilyas, Muhammad (International Journal Of Community Medicine And Public Health, 2024)
Background: Cigarette smoking disrupts sleep patterns. Studies suggest a strong link between sleep quality and academic achievement. This study investigates the impact of smoking on sleep quality and academic performance, informing the importance of smoking cessation strategies. Methods: A cross-sectional, questionnaire-based study was conducted among 100 medical students of Nishtar Medical University from June 2023 to March 2024, using a convenient sampling technique. Demographic and anthropometric details were obtained, and academic performance was recorded based on the percentage achieved in the recent professional examination. Sleep quality was assessed by a validated questionnaire; PSQI. SPSS version 27 was utilized for data analysis. Results: Smokers demonstrated a significantly higher PSQI (median 7, IQR 2-13) than non-smokers (median 4, IQR 1-15), p= 0.02. Academic scores were slightly higher in non-smokers (median 73.5, IQR 59.35-81.85) than in smokers (median 69.85, IQR 51-78.5), p= 0.05. In Group 1 (nonsmokers) and Group 2 (smokers), there was a significant negative correlation between PSQI and academic performance (Rho = -0.357, p = 0.011), and (Rho = -0.314, p = 0.026) respectively. Cigarettes smoked per day were also significantly correlated with both PSQI (Rho = 0.331, p = 0.019) and academic performance (Rho = -0.539, p = 0.000). Conclusions: Smokers had poor sleep quality and slightly lower academic scores than non-smokers. Poor sleep quality was strongly tied to lower academic achievement. Students should be informed about the link between cigarette smoking and poor sleep quality, and how that affects academic performance.